Vitamin D levels and vitamin D receptor gene polymorphisms in asthmatic children: a case–control study1. Issue 6 (17th June 2015) - Einisman, Helly; Reyes, María Loreto; Angulo, Jenniffer; Cerda, Jaime; López‐Lastra, Marcelo; Castro‐Rodriguez, Jose A.
Abstract Background Vitamin D deficiency and single nucleotide polymorphisms (SNP) in the gene encoding vitamin D receptor (VDR) have been associated with asthma. Objective To compare 25‐hydroxyvitamin D (25OHD) levels and the frequency of 3 SNPs in the VDR gene between asthmatic and healthy children. Methods In persistent asthmatic and healthy control children, the 25OHD levels were measured using radioimmunoassay and SNPs (FokI, ApaI, and TaqI) were analyzed by a PCR‐RFLP assay. Relevant medical history was collected. Results About 75 asthmatic (median age: 9.1 years) and 227 healthy children (10.3 years) were studied. In the whole population, the proportion of sufficient, insufficient, and deficient levels of 25OHD were 14.9%, 44%, and 41.1%, respectively. 25OHD sufficiency status was similar in asthmatic and healthy children (p = 0.57). However, the proportion of 25OHD sufficient levels among asthmatics according to the Global Initiative for Asthma treatment steps 2, 3, and 4 was significantly different (8.6%, 16.6%, and 43.7%, respectively, p = 0.046). All patients on step 4 of the treatment (16/16) were heterozygous for the C allele (FokI VDR SNP). There was a lower presence of the C allele among asthmatics in step 2 (30/33), step 3 (16/24), and controls (45/50), p = 0.007, but this significance did not persist after logistic regression. No significant differences in ApaI and TaqI were found. Conclusions We found a possible association of vitamin D sufficiency status and FokI C allele with higher requirement of therapy to reach asthma control, suggesting that it may be involved in treatment response. Variations in VDR might also play a role in the 25OHD levels.